Metal-Support Interaction and Charge Distribution in Ceria-Supported Au Particles Exposed to CO - Bezkrovnyi, Oleksii; Bruix, Albert; Blaumeiser, Dominik; Piliai, Lesia; Schötz, Simon; Bauer, Tanja; Khalakhan, Ivan; Skála, Tomáš; Matvija, Peter; Kraszkiewicz, Piotr; Pawlyta, Mirosława; Vorokhta, Mykhailo; et al. (Chemistry of materials, 2022)
Understanding how reaction conditions affect metal-support interactions in catalytic materials is one of the most challenging tasks in heterogeneous catalysis research. Metal nanoparticles and their supports often undergo changes in structure and oxidation state when exposed to reactants, hindering a straightforward understanding of the structure-activity relations using only ex situ or ultrahigh vacuum techniques. Overcoming these limitations, we explored the metal-support interaction between gold nanoparticles and ceria supports in ultrahigh vacuum and after exposure to CO. A combination of in situ methods (on powder and model Au/CeO2 samples) and theoretical calculations was applied to investigate the gold/ceria interface and its reactivity toward CO exposure. X-ray photoelectron spectroscopy measurements rationalized by first-principles calculations reveal a distinctly inhomogeneous charge distribution, with Au+ atoms in contact with the ceria substrate and neutral Au0 atoms at the surface of the Au nanoparticles. Exposure to CO partially reduces the ceria substrate, leading to electron transfer to the supported Au nanoparticles. Transferred electrons can delocalize among the neutral Au atoms of the particle or contribute to forming inert Auδ- atoms near oxygen vacancies at the ceria surface. This charge redistribution is consistent with the evolution of the vibrational frequencies of CO adsorbed on Au particles obtained using diffuse reflectance infrared Fourier transform spectroscopy.